1997
DOI: 10.1128/jb.179.18.5693-5698.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic responses of the thermophilic archaeon Sulfolobus acidocaldarius to short-wavelength UV light

Abstract: The archaea which populate geothermal environments are adapted to conditions that should greatly destabilize the primary structure of DNA, yet the basic biological aspects of DNA damage and repair remain unexplored for this group of prokaryotes. We used auxotrophic mutants of the extremely thermoacidophilic archaeon Sulfolobus acidocaldarius to assess genetic and physiological effects of a well-characterized DNAdamaging agent, short-wavelength UV light. Simple genetic assays enabled quantitative dose-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Our results showed that T. kodakaraensis cells are originally more sensitive to UV, as compared to other archaeal species, such as S. solfataricus (Wood et al, 1997), H. volcani (McCready, 1996, and Halobacterium sp. NRC-1 (Baliga et al, 2004), and are also more sensitive than typical model organisms, such as E. coli (Shibata et al, 2005), and Saccharomyces cerevisiae (Hishida et al, 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Our results showed that T. kodakaraensis cells are originally more sensitive to UV, as compared to other archaeal species, such as S. solfataricus (Wood et al, 1997), H. volcani (McCready, 1996, and Halobacterium sp. NRC-1 (Baliga et al, 2004), and are also more sensitive than typical model organisms, such as E. coli (Shibata et al, 2005), and Saccharomyces cerevisiae (Hishida et al, 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Among thermophilic archaea, the greatest number of genetic processes occur in members of the genus Sulfolobus ; for example, spontaneous mutation (Jacobs & Grogan, 1997), UV-induced mutation (Wood et al, 1997) and photoreactivation (Grogan, 1997) have been studied in Sulfolobus acidocaldarius. Moreover, S. acidocaldarius spontaneously exchanges and recombines chromosomal genetic markers (Grogan, 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…Most organisms repair these lesions in two ways-lightdependent photoreactivation catalyzed by a photolyase, and light-independent nucleotide excision repair (NER). Although both mechanisms can repair the two kinds of damage, photoreactivation is more efficient in repairing CPDs, whereas NER is more effective in repairing (6-4) photoproducts (Friedberg 1995).Several archaea, including Halobacterium NRC-1, are capable of photoreactivation (McCready 1996;Wood et al 1997). Of the two photolyase-homologs, phr1 and phr2, in Halobacterium NRC-1, at least one, phr2, encodes an active CPD photolyase.…”
mentioning
confidence: 99%
“…Several archaea, including Halobacterium NRC-1, are capable of photoreactivation (McCready 1996;Wood et al 1997). Of the two photolyase-homologs, phr1 and phr2, in Halobacterium NRC-1, at least one, phr2, encodes an active CPD photolyase.…”
mentioning
confidence: 99%